2020
DOI: 10.12688/f1000research.21310.2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant, antibacterial and wound healing activities of Vitex pinnata

Abstract: Background: Vitex pinnata is a popular ethnomedicinal plant but scientific studies to validate its pharmacological properties are lacking for this plant. This study aims to determine the antioxidant, antimicrobial and wound healing properties of the methanolic extract of the leaves and the hexane, chloroform and ethyl acetate fractions.    Methods: The leaves of Vitex pinnata underwent methanol extraction and the methanol extract was fractionated with hexane, chloroform and ethyl acetate solvents. The antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This study was aimed at determining whether the leaf extract of V. pinnata could be a good source of antioxidants or not. Results showed that the leaf extract of V. pinnata contained antioxidants, which was supported by other studies (Shafie et al 2020).…”
Section: Discussionsupporting
confidence: 85%
“…This study was aimed at determining whether the leaf extract of V. pinnata could be a good source of antioxidants or not. Results showed that the leaf extract of V. pinnata contained antioxidants, which was supported by other studies (Shafie et al 2020).…”
Section: Discussionsupporting
confidence: 85%
“…It indicated that V. pinnata Linn leaves have a wide range of semi-polar compounds, such as polyphenolic compounds of flavonoids [37][38]. High contents of phenolic content in the ethyl acetate fractions were also reported by Shafie et al [39] working with Vitex pinnata leaves (33.1 ± 0.1 mg QE/g), de Brum et al [40] working with Vitex megapotamica leaves (522.4 ± 1.12 mg GAE/g), Gothai et al [41] with Moringa oleifera leaves (65.81 ± 0.01 mg GAE/g ), Lasboi et al [42] with Muntingia calabura L leaves (74.90 mg GAE/g), Okselni et al [43] with Elaeocarpus mastersii Kings roots, leaves, and stem bark (362.88 ± 1.89 mg GAE/g, 380.99 ± 2.14 mg GAE/g, and 341.89 ± 3.97 mg GAE/g ), and studies Tinco-Jayo et al [44] with Jatropha macrantha Müll Arg. L leaves and stems (359 ± 5.21 mg GAE/g and 306 ± 1.93 mg GAE/g).…”
Section: Extractionmentioning
confidence: 63%
“…This study was conducted in Ayer Hitam Utara Forest Reserve, Johor. This forest reserve was categorized as Protected Area and also one of the largest and last remaining peat swamp forests in Johor [8]. It is a 3,965.84 hectares (ha) forest reserve in Muar district of Johor [8].…”
Section: Methodology 21 Study Sitementioning
confidence: 99%
“…Allomorphia alata, Syzygium papillosum, Vitrex pinnata are traditionally used stomachache using traditional knowledge [11] [8] [21]. Ochanostachys amentacea, Syzygium papillosum, Vitrex pinnata are other examples in treating stomachache by using the traditional knowledge [8] [21]. In most of treatment it usually leaves with the decoction method to treat certain diseases.…”
Section: Spondiasmentioning
confidence: 99%